Analyzing exercise-to-rest ratios in U19 American football European championship: implications for team success and injury prevention - Valentin Prioul; Valentin Prioul; Jean Slawinski; Steeve Guersent; Laure Le Monnier; Vincent Goeb; Florent Krim; Philippe Lopes; Pierre-Marie Leprêtre; Pierre-Marie Leprêtre (Frontiers in Sports and Active Living)
BackgroundThe teams' collective playing strategy rather than the individual player attitudes could explain event outcome and risk of injuries.ObjectiveThe study aimed to examine the playing style of European teams and compare it to the USA.Method12 matches from the U19 European championship of American Football were analysed. We characterized each team by their running-passing activities ratio during the offensive phase: running (RUN), passing (PASS), or balanced (BAL).ResultsThe BAL style of play accurately described 75% of European teams (n = 6). The remaining two national teams adopted either the RUN or PASS style of play. This finding is similar to what was observed in NCAA Division IA. All RUN style teams had a higher percentage of rushing plays (80.7% ± 9.7%) compared to PASS (33.0% ± 14.7%) and BAL teams (46.0 ± 0.8%) (p < 0.05). The mean playing time for RUN and PASS teams was longer than the average duration of plays for BAL teams (p < 0.05). The mean duration of plays ranged from 5.3 ± 1.9 to 5.7 ± 2.1 s, with a significant style of play effect (p < 0.05). Rest duration for BAL teams (46.7 ± 44.1 s) was shorter than that of RUN (55.9 ± 34.7 s) and PASS (54.5 ± 32.9 s) teams (p < 0.05). Finally, the European top final team was the team that was able to shift their game style during the tournament and presented a low coefficient of variation in offensive plays per drive.ConclusionBased on the running-passing activities ratio, the video match analysis can provide a foundation for the strength and conditioning program for long-term athlete development and injury prevention.